Association between the DASH diet and Alzheimer’s disease in a case-control study - Mohammad Mehdi Abbasi; Sajjad Khandae; Mahshad Shahabi; Mousa Attarzadeh; Mahdiyeh Karimi; Hoora Saghafi; Soodeh Razeghi; Fatemeh Khamseh; Bahram Rashidkhani (Scientific Reports)
Abstract The findings on the connection between Alzheimer’s disease and the dietary approaches to stop hypertension (DASH) are inconsistent. Additionally, the relationship between Alzheimer’s and the DASH diet has not been explored in the Middle East region. This case-control study aimed to evaluate the association between adherence to DASH diet and the risk of Alzheimer’s disease. The study included 212 participants (106 cases and 106 controls). Cases were recruited among people in the early stages of the disease who had been diagnosed with Alzheimer’s disease within the past six months. Controls were selected from health centers across Tehran. Dietary intake was assessed using a validated 168-item food frequency questionnaire. Four DASH diet indices (Dixon, Mellen, Fung, and Günther) were used to evaluate the adherence. After adjusting for potential confounders, higher adherence to Günther’s, Mellen’s, and Fung’s DASH diet indices were significantly associated with a reduced risk of Alzheimer’s disease (Mellen’s OR: 0.29; 95% CI: 0.10–0.83; Fung’s OR: 0.22; 95% CI: 0.08–0.65; Günther’s OR: 0.36; 95% CI: 0.13–1.00). Adherence to DASH dietary pattern might be associated with a decreased risk of Alzheimer’s disease. Future studies should aim to investigate the association in a prospective design in the Middle East.